Monastery of Salzedas (Portugal): intervention in the cloister and information management - Lourenço, Paulo B. (2008)
Anyone involved in the conservation of cultural heritage buildings is aware of the enormous amount of information generated by the different specialists, which is generally not handled adequately by owners and/or authorities involved in the process. The consequence is that valuable information is lost in a complex process of reaching a decision that involves many different experts and information tends to get forgotten or misplaced in the course of time. A case study with extensive damage, which recently suffered significant conservation works, is described in detail, so that the adopted remedial measures are justified. Then, the case study is also used to develop an application for the efficient management and visualization of the information related to interventions of cultural heritage buildings.